All‐Rounder Low‐Cost Dopant‐Free D‐A‐D Hole‐Transporting Materials for Efficient Indoor and Outdoor Performance of Perovskite Solar Cells. (15th January 2020) - Pham, Hong Duc; Jain, Sagar M.; Li, Meng; Wang, Zhao‐Kui; Manzhos, Sergei; Feron, Krishna; Pitchaimuthu, Sudhagar; Liu, Zhiyong; Motta, Nunzio; Durrant, James R.; Sonar, Prashant
Abstract: A novel biphenyl fumaronitrile as an acceptor and triphenylamine as donor conjugated building blocks are used for the first time to successfully synthesize donor–acceptor–donor molecule (D‐A‐D) 2, 3‐bis(4′‐(bis(4‐methoxyphenyl)amino)‐[1, 1′‐biphenyl]‐4‐yl)fumaronitrile (TPA‐BPFN‐TPA). The new TPA‐BPFN‐TPA with low‐lying HOMO is used as a dopant‐free hole‐transporting material (HTM) in mesoporous perovskite solar cells. The performance of the solar cells using this new HTM is compared with the traditional 2, 2′, 7, 7′‐tetrakis( N, N ′‐di‐p‐methoxyphenylamino)‐ 9, 9′‐spirobifluorene (Spiro‐OMeTAD) HTM based devices for outdoor and indoor performance evaluation. Under 1 sun illumination, dopant‐free TPA‐BPFN‐TPA HTM based devices exhibit a power conversion efficiency (PCE) of 18.4%, which is the record efficiency to date among D‐A‐D molecular design based dopant‐free HTMs. Moreover, the stability of unencapsulated TPA‐BPFN‐TPA‐based devices shows improvement over Spiro‐OMeTAD‐based devices in harsh relative humidity condition of 70%. Another exciting feature of the newly developed HTM is that the TPA‐BPFN‐TPA‐based devices exhibit improved PCE of 30% and 20.1% at 1000 lux and 200 lux illuminations, respectively. This new finding provides a solution to fabricate low indoor (low light) and outdoor (1 sun) perovskite solar cell devices with high efficiency for cutting‐edge energy harvesting technology. Abstract : A novel dopant‐free donor–acceptor–donor hole‐transporting material TPA‐BPFN‐TPA is developed and fabricated successfully in mesoporous CH3 NH3 PbI3 devices for the first time. TPA‐BPFN‐TPA‐based devices exhibit an efficiency of 18.4% without hysteresis. The resulting devices exhibit an excellent indoor performance, with efficiencies of 30.01% and 20.1% under fluorescent lamps at 1000 lux and 200 lux illuminations, respectively.